2011
DOI: 10.2139/ssrn.2236718
|View full text |Cite
|
Sign up to set email alerts
|

Real Exchange Rates, Trade, and Growth: Italy 1861-2011

Abstract: The purpose of the Economic History Working Papers (Quaderni di Storia economica) is to promote the circulation of preliminary versions of working papers on growth, finance, money, institutions prepared within the Bank of Italy or presented at Bank seminars by external speakers with the aim of stimulating comments and suggestions. The present series substitutes the Historical Research papers -Quaderni dell'Ufficio Ricerche Storiche. The views expressed in the articles are those of the authors and do not involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 85 publications
(151 reference statements)
5
31
0
1
Order By: Relevance
“…This study reveals that positive growth of official exchange rate negatively affects the RMG export growth of Bangladesh. Evidence supports that weak currency or lower exchange rate and economic growth are positively related to each other (Di Nino, Eichengreen, & Sbracia, 2011). This study shows that positive growth of inflation rate negatively affects the RMG export growth.…”
Section: Discussionsupporting
confidence: 66%
“…This study reveals that positive growth of official exchange rate negatively affects the RMG export growth of Bangladesh. Evidence supports that weak currency or lower exchange rate and economic growth are positively related to each other (Di Nino, Eichengreen, & Sbracia, 2011). This study shows that positive growth of inflation rate negatively affects the RMG export growth.…”
Section: Discussionsupporting
confidence: 66%
“…Here we argue for the opposite channel: a capital in ‡ow shock appreciates the real exchange rate, and we want to test is this appreciation reduces growth. 14 We also split countries according to whether they have negative or positive net foreign asset positions, using the data of Lane and Shambaugh (2010) and Benetrix et al (2015) (not reported for brevity). It can…”
Section: The Empirical Modelmentioning
confidence: 99%
“…According to Habib et al (2017), whilst politicians are often convinced that a lower exchange rate will spur economic growth, economists on the other hand are generally skeptical that the relative price of two currencies may be a fundamental driver of economic growth over the long run. However, several studies have put forth theoretical arguments in favour of this relationship, see studies done by Rodrik (2008), Aizenman and Lee (2010), Di Nino et al (2011), McLeod and Mileva (2011) and Glüzmann et al (2012). Whilst on the other hand, there has been a plethora of empirical literature in recent times confirming this relationship, see Aguirre and Calderón (2005), Rodrik (2008), Rapetti et al (2012), Béreau et al (2012) and Missio et al (2015).…”
Section: Literature Review: the Relationship Between Real Exchange Ramentioning
confidence: 97%